Does gender influence how patients rate their patient experience after total hip arthroplasty?. Issue 1 (January 2018) - Delanois, Ronald E.; Gwam, Chukwuweike U.; Mistry, Jaydev B.; Chughtai, Morad; Khlopas, Anton; Yakubek, George; Ramkumar, Prem N.; Piuzzi, Nicolas S.; Mont, Michael A.
Background: Patient satisfaction, as measured by Press Ganey (PG) surveys, partially determines reimbursement rates. Knowing what influences these scores can lead to higher reimbursement for total hip arthroplasty (THA) surgeons. Currently, it is unknown whether gender biases exist in satisfaction surveys post-THA. Therefore, we asked: (i) which PG survey factors most influence hospital ratings among men and women after THA; and (ii) is there a difference in survey element responses and overall hospital ratings between men and women post-THA? Methods: We queried the PG database for patients who underwent THA from November 2009 to January 2015, which yielded 692 patients (277 men, 415 women). Weighted means were analysed for the scores of PG domains between men and women. A multiple regression analysis was performed for each gender, with overall hospital satisfaction as the dependent variable, in order to assess the influence (β-weight) of each PG domain. Results: For men, pain management (β = 0.317, p = 0.021) most influenced overall hospital rating. For women, staff responsiveness (β = 0.451, p<0.001) most influenced overall hospital rating. This was followed by communication with nurses (β = 0.373, p<0.001), and doctors (β = 0.236, p = 0.002). There were no significant differences in mean overall hospital rating between groups. Conclusions: It is advantageous for orthopaedic surgeons to focus on the PG domains most pertinent to each patient gender post-THA. Focusing efforts based on gender may allow for better patient satisfaction, optimised reimbursements, and improved hospital ratings.